Investigation of Retired Elite Athletes’ Food Addiction - Kalkan, Naci (Progress in Nutrition, 2022)
The aim of this study is to examine the food addiction levels of retired elite athletes in terms of various variables. The research is a descriptive cross-sectional study. The sample group of the study, fencing, football, basketball, volleyball, athletics, handball, tae-kwon-do, badminton and tennis, who ended their sports career at least 3 years ago, 51 men (53.1%) and 45 women (46.9%) average age 33.75 ± 5.88 total 96 constitute the national athlete. In the study, Yale Food Addiction Scale consisting of 27 questions developed by Gearhardt et al. in 2009 and adapted to Turk-ish by Bayraktar et al. In 2012 was applied to the participants in the study. Food addiction was detected in 39 of 96 participants participating in the study. When the data obtained in the study were examined, it was de-termined that the athletes who retired after exercising at the elite level experienced higher levels of problems with food addiction compared to other members of the society